Silybin Alleviates Experimental Autoimmune Encephalomyelitis by Suppressing Dendritic Cell Activation and Th17 Cell Differentiation - Yang, Huan-Li; Shi, Xiao-Wu (Frontiers in Neurology, 2021)
Silybin, a peculiar flavonoid compound derived from the fruit and seeds of Silybum marianum. In the present study, we demonstrated that silybin effectively alleviated experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), via involving inhibition of dendritic cells (DCs) activation and Th17 cell differentiation. Silybin treatment greatly ameliorated the severity of the disease and significantly declined inflammation and demyelination of the central nervous system (CNS) in EAE mice. Consistent with the disease development, silybin-treated, bone marrow-derived dendritic cells (BM-DCs) showed reduced expression of costimulatory molecules (e.g., CD80 and CD86) and MHC II expression. These results, showed the activity of silybin to weaken DC activation, inhibiting pathogenic Th17 inflammatory cell responses and, eventually, alleviating EAE severity. Taken together, our results show that silybin has huge potential for development as a therapeutic agent for autoimmune diseases such as MS.